2022
DOI: 10.7759/cureus.26017
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study Between Amiodarone and Implantable Cardioverter-Defibrillator in Decreasing Mortality From Sudden Cardiac Death in High-Risk Patients: A Systematic Review and Meta-Analysis

Abstract: Sudden cardiac death (SCD) is an unexpected death that occurs within one hour of symptom onset. In the United States, sudden cardiac death is considered the leading cause of natural death, accounting for 325,000 adult patients annually. SCD is more common in adult patients (above the mid-30s) and men. The risk factors that predict SCD are categorized into clinical, sociological, genetic, and psychological. To prevent the occurrence of SCD, several treatment options, especially antiarrhythmic drugs and implanta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Additionally, the use of amiodarone in treating patients with an increased risk of sudden cardiac deaths, such as those with heart failure, has also been associated with high all-cause mortality rates. Our recent meta-analysis comparing the effectiveness of implantable cardioverter-defibrillator (ICD) to amiodarone in decreasing mortality from sudden cardiac deaths showed that amiodarone was highly associated with all-cause mortality compared with ICD (OR: 1.36; 95% CI: 1.06 to 1.74; I 2 = 57%; p = 0.03) [ 36 ].…”
Section: Reviewmentioning
confidence: 99%
“…Additionally, the use of amiodarone in treating patients with an increased risk of sudden cardiac deaths, such as those with heart failure, has also been associated with high all-cause mortality rates. Our recent meta-analysis comparing the effectiveness of implantable cardioverter-defibrillator (ICD) to amiodarone in decreasing mortality from sudden cardiac deaths showed that amiodarone was highly associated with all-cause mortality compared with ICD (OR: 1.36; 95% CI: 1.06 to 1.74; I 2 = 57%; p = 0.03) [ 36 ].…”
Section: Reviewmentioning
confidence: 99%